Advances in nano and biochemistry : environmental and biomedical applications - Morajkar, Pranay Pradeep (Progress in biochemistry and biotechnology, 2023)
Advances in Nano and Biochemistry: Environmental and Biomedical Applications gives insights into this advanced interdisciplinary science that encompasses the principles of physics and physical chemistry for the investigation of various processes and problems in biological systems.